FAKTOR-FAKTOR YANG MEMPENGARUHI PELAYANAN PT.PLN (Persero) PROVINSI RIAU - Viloura Fessilanda; Chalid Sahuri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Factors that influence services in PT. PLN (Persero) Riau Province. The purpose of this research is to find out factors that influence services in PT. PLN (Persero) Riau Province. This research is conducted in area of Pekanbaru city with the PT. PLN (Persero) Riau Province office as analysis unit. The factors are measured in four indicators: organizational structure, the ability of officers, service system, and service infrastructure. This is a qualitative descriptive research. Data collecting technique are observation, interview, and documentation. Result shows that organizational structure of PT. PLN (Persero) meets the standard of Direction Board of PT. PLN (Persero) Riau province. The ability of the officers meet the procedural requirements, the staffs are well behave to the complaining customers. Service system can be seen from the easy access all over the area, services available, and the good order of the services, and infrastructure used so PT. PLN (Persero) can deliver the services faster, easier, and more accurate.Key word: Services factors, organizational structure, ability of officers, services system, and service infrastructure.